Construction and validation of the educational booklet for nurses about pressure injuries (Research, Society and Development, 2021)
Objective: to build and validate an educational booklet for nurses about pressure injuries. Method: methodological study, developed in three stages - integrative review, preparation of booklet, and validation by specialists in the subject and representatives of the target audience. Validation was carried out by 8 judges and 39 representatives of the target audience. The Minimum Content Validity Index of 0.80 was considered for content validation and minimum agreement of 75% for appearance validation. Results: The booklet presented a global Content Validity Index of 0.90 by the judges and an excellent level of agreement between the judges (87% -100%) and representatives of the target audience (96% -100%). However, the judges proposed suggestions for improving the booklet, which were accepted and modified for the final version of the material. Conclusion: the educational booklet was validated in terms of content and appearance, and should be considered in the context of educational activities as an instrument capable of favoring nurses in the prevention and treatment of pressure injuries.